Data, Predictive Maintenance Promise Operational Benefits. Issue 4 (2nd April 2020) - Howley, Andrew Chastain; Stillman, Jeff
Abstract : The water and wastewater industry is under growing pressure from expanding populations, aging infrastructure, falling revenues, and extreme weather events caused by climate change. Although new infrastructure will play a large role in positioning the industry for a more sustainable, resilient future, utilities now have the opportunity to harness and use data to improve the performance of existing assets, helping them achieve operational goals.